NURSING CARE FOR AUTISM SPECTRUM DISORDER PATIENTS: LITERATURE REVIEW - Feifer, Gabrielle Palma; de Souza, Thalita Borges; Mesquita, Leticia Ferreira; Oliveira Ferreira, Anna Rebeka; Machado, Marcio Fraiberg (Revista Uningá, 2020)
The Autism Spectrum Disorder is predominantly in children and, in Brazil, the frequency is 1 in 68 individuals. In 2016, 63,000 cases of autistic children were performed in the state of Paraná, making it essential for professionals to be able to attend to patients, performing previous diagnoses and favoring more effective treatment. The aim of this study is analyze the scientific production related to nursing care and multiprofessional provided to people with Autism Spectrum Disorder. This is a review of the literature, using as inclusion criteria articles in Portuguese related to the topic addressed, published in the year 2007 to 2017, found in the Scientific Electronic Library Online, Virtual Health Library and Coordination for the Improvement of Higher Education Personnel. The analysis articles selected were grouped into four categories; the first one: Health Education Strategies; the second: Multiprofessional understanding of reality; the third: Nurses' perception about Autism Spectrum Disorder; fourth: Nursing care in the care of the patient and use of nursing processes. It can be verified that professionals have a need to increase their knowledge about this topic, to base their actions of protection and education in health, so that the early diagnosis can be performed, however it is necessary to carry out capacity building, so that professionals can provide comprehensive care for both the patient and the family, in order to improve the quality of life of both.